A population pharmacokinetic model of AT9283 in adults and children to predict the maximum tolerated dose in children with leukaemia. (5th March 2017) - Duong, Janna K.; Griffin, Melanie J.; Hargrave, Darren; Vormoor, Josef; Edwards, David; Boddy, Alan V.
Abstract : Aims: AT9283 is used to treat patients with solid tumours and patients with leukaemia. However, the maximum tolerated dose (MTD) for children with leukaemia remains unknown due to early termination of the Phase I trial. The aim of this study was to develop a population model of AT9283 to describe the pharmacokinetics in adults and children and to estimate the MTD in children with leukaemia. Methods: Data from Phase I dose‐escalation studies in adults and children were used to build a population pharmacokinetic model (NONMEM v7.3). Potential covariates investigated included body weight, body surface area (BSA), glomerular filtration rate (GFR), age and sex. Model‐derived area under the concentration–time curve was used to investigate the relationship between dose and exposure in adults and children. Results: The plasma concentrations of AT9283 ( n = 1770) from 92 patients (53 adults, 39 children) were used to build a two‐compartment model with all pharmacokinetic parameters scaled using body weight. Renal function (GFR), but not BSA, was a significant covariate for the clearance of AT9283. In children with leukaemia (median weight 16 kg), a flat dose of 500 mg 72 h –1 provided similar drug exposures at the MTD as the adult population. The estimated MTD for children with leukaemia, therefore, is 30 mg kg −1 72 h –1 . Conclusion: For adults, GFR was a significant predictor of clearance, whilst body‐weight based dosing was more useful than BSA in determining the drug exposure in children. The MTD was estimated to be 30 mg kg −1 72 h –1 children with leukaemia.